DEPRESSION, ANXIETY AND STRESS AMONG ALCOHOL ADDICTS - Barać, Stevan V; Gutić, Medo; Vukčević, Branimir; Safiye, Teodora; Radmanović, Branimir; Đorđić, Milan; Sekulić, Marija; Stajić, Dalibor; Joksimović, Stefan; Đoković, Danijela D.; Samardžić, Snežana (Medicinski časopis, 2022)
ABSTRACT Objective. The aim of the study was to examine the level of depression, anxiety and stress in alcohol addicts, ie to determine differences in the level of depression, anxiety and stress between the group of subjects diagnosed with F10.1 and the group of subjects diagnosed with F10.2, as well as to determine differences in sociodemographic characteristics, and health status between groups of subjects diagnosed with F10.1 and F10.2. Methods. Our study was designed as a non-experimental, observational cross-sectional study. Our study was conducted at the University Clinical Center Kragujevac in the Clinic for Psychiatry, during January 2021. The sample consisted of 110 respondents of both sexes, aged 18 to 65, divided into two groups. The first group consisted of subjects diagnosed with alcohol dependence (F10.2), and the second group consisted of subjects diagnosed with alcohol abuse (F10.1). Results. Our study has shown that alcohol addicts have clinically significant and severe symptoms of depression, that symptoms were positively correlated with stress levels, and that short-term stress of milder intensity was associated with occasional alcohol abuse, while prolonged stress was a predictor of alcohol dependence. No statistically significant association of alcohol dependence and alcohol abuse with anxiety was found. It was also found that alcohol dependence is associated with certain sociodemographic characteristics such as gender and marital status, education level, employment status, as well as health status and number of hospitalizations. Conclusion. With this study, we have shown how much stress is present and important in the genesis of alcoholism, then the positive correlation of depression and alcohol dependence, as well as the importance of sociodemographic characteristics in their genesis. Key words: alcohol abuse, alcohol dependence, stress, anxiety, depression